Fermenting Sculptures: Edges and Encounters of the Vessel and the Body - Nash, S. (Cuizine)

(untitled) (McGill University Library, 2018)
The significance of microbes in relation to a queer perspective on being is central to my thought process around this work. They/Them/Their was titled in reference to my gender pronouns and also to the multitude of microbes we coexist with. When framing the human in relation to prokaryotes (bacteria), we learn that they outnumber us in our own bodies as well as in the population on Earth, not just in numbers of individuals, but in total biomass as well. Microbes reproduce in myriad ways and cannot be defined by gender. If microbes are without gender and they make up at least half of our human selves, then are we are all pluralities? Are we are all they, them, and their?